The UK Leicester COVID-19 'exceedance' May–July 2020: An analysis of hospitalised cases. Issue 1 (July 2021) - Tang, Julian W; Bird, Paul W; Holmes, Christopher W; Nicoara, Daniela C; Woltmann, Gerrit; Haldar, Pranabashis; Holmes, Nadine; Carlile, Matthew; Moore, Christopher; McClure, Patrick; Loose, Matthew
Highlights: In June 2020, Leicester was the first city in the UK to go into a local lockdown, as community COVID-19 cases remained high. In contrast to this community (Pillar 2) data, the hospitalised (Pillar 1) COVID-19 case counts continued to remain low. A Public Health England phylogenetic analysis of Pillar 2 sample sequences did not find any specific pattern of transmission. Here we perform a complementary phylogenetic analysis of Pillar 1 sample sequences, tagged with anonymised metadata. We found no specific pattern of transmission between any of the metadata related to these hospitalised COVID-19 patients.